2020
DOI: 10.1111/bph.15286
|View full text |Cite
|
Sign up to set email alerts
|

Screening for liver X receptor modulators: Where are we and for what use?

Abstract: Liver X receptors (LXRs) are members of the nuclear receptor superfamily that are canonically activated by oxidized derivatives of cholesterol. Since the mid-90s, numerous groups have identified LXRs as endocrine receptors that are involved in the regulation of various physiological functions. As a result, when their expression is genetically modified in mice, phenotypic analyses reveal endocrine disorders ranging from infertility to diabetes and obesity, nervous system pathologies such Alzheimer's or Parkinso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 124 publications
0
21
0
Order By: Relevance
“…Some of our results are at odds with prior observations. We were unable to detect expression of XP_02430405X (previously termed a4 (Endo-Umeda et al, 2012)), in any cell lines or tissues, at RNA or protein level, including in HEPG2 or MCF7 cell lines that were previously shown to express this isoform (Bunay et al, 2020;Endo-Umeda et al, 2012). Intriguingly, a variant previously reported to be a5 (Bunay et al, 2020;Endo-Umeda et al, 2012) did not correspond to any of the 64 LXRa transcripts from NCBI nor any LXRa UNIPROT entries.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Some of our results are at odds with prior observations. We were unable to detect expression of XP_02430405X (previously termed a4 (Endo-Umeda et al, 2012)), in any cell lines or tissues, at RNA or protein level, including in HEPG2 or MCF7 cell lines that were previously shown to express this isoform (Bunay et al, 2020;Endo-Umeda et al, 2012). Intriguingly, a variant previously reported to be a5 (Bunay et al, 2020;Endo-Umeda et al, 2012) did not correspond to any of the 64 LXRa transcripts from NCBI nor any LXRa UNIPROT entries.…”
Section: Discussionmentioning
confidence: 62%
“…We were unable to detect expression of XP_02430405X (previously termed a4 (Endo-Umeda et al, 2012)), in any cell lines or tissues, at RNA or protein level, including in HEPG2 or MCF7 cell lines that were previously shown to express this isoform (Bunay et al, 2020;Endo-Umeda et al, 2012). Intriguingly, a variant previously reported to be a5 (Bunay et al, 2020;Endo-Umeda et al, 2012) did not correspond to any of the 64 LXRa transcripts from NCBI nor any LXRa UNIPROT entries. In this study (Endo-Umeda et al, 2012), the measurement of XP_02430405X and previously reported a5 relied on PCR primers that detected a retained intron between exon 6-7 and a retained intron between exon 7-8, respectively (see Figure S3).…”
Section: Discussionmentioning
confidence: 62%
“…Some of our results are at odds with prior observations. We were unable to detect expression of XP_02430405X (previously termed a4 [16]), in any cell lines or tissues, at RNA or protein level, including in HEPG2 or MCF7 cell lines that were previously shown to express this isoform [16,33]. Intriguingly, a variant previously reported to be a5 [16,33] did not correspond to any of the 64 LXRa transcripts from NCBI, nor any LXRa UNIPROT entries (SF2A).…”
Section: Belorusova Et Al Reported Peptides Of Lxrα Comprising the H3 And Partial Part Of H5mentioning
confidence: 66%
“…We were unable to detect expression of XP_02430405X (previously termed a4 [16]), in any cell lines or tissues, at RNA or protein level, including in HEPG2 or MCF7 cell lines that were previously shown to express this isoform [16,33]. Intriguingly, a variant previously reported to be a5 [16,33] did not correspond to any of the 64 LXRa transcripts from NCBI, nor any LXRa UNIPROT entries (SF2A). In this study [16], the measurement of XP_02430405X and previously reported a5 relied on PCR primers that detected a retained intron between exon 6-7 and a retained intron between exon 7-8, respectively (SF2A).…”
Section: Belorusova Et Al Reported Peptides Of Lxrα Comprising the H3 And Partial Part Of H5mentioning
confidence: 66%
“…Strategies for improving the efficacy and safety of these therapeutic drugs have been actively developed [109][110][111]. Statins can also be classified as anti-cancer agents that inhibit lipid raft-mediated Akt signalling [71,73,103,104].…”
Section: Therapeutic Approaches Targeting Lipid Raft Dynamics Through Primary Ciliamentioning
confidence: 99%